Involvement of DNA methylation in regulating the accumulation of the aroma compound indole in tea (Camellia sinensis)leaves during postharvest processing - Yang, J.; Zhou, X.; Wu, S.; Gu, D.; Zeng, L.; Yang, Z.
The manufacturing process of tea (Camellia sinensis), especially oolong tea, involves multiple postharvest stresses. These stresses can induce the formation and accumulation of many important aroma compounds, such as indole-a key floral aroma contributor of oolong tea. However, little is known about the regulation mechanisms of aroma compound formation, especially epigenetic regulation. DNA methylation is an important epigenetic modification. Changes in the DNA methylation levels of promoter sequences can regulate gene expression under stress conditions. In this study, the differences in DNA methylation levels and histone 3 lysine 9 dimethylation levels of indole key biosynthetic gene (tryptophan synthase ?-subunit 2, CsTSB2)were detected between untreated and continuous wounding treatment tea leaves. The results show that the DNA methylation levels affect the ability of the basic helix-loop-helix family transcription factor CsMYC2a to bind to the promoter of CsTSB2. Analyses of the transcript levels of DNA methyltransferases during oolong tea processing screened out candidate genes involved in the regulation of secondary metabolite product biosynthesis/accumulation. The results suggest that the domains rearranged methyltransferase 3, a DNA methyltransferase, is involved in the DNA methylation regulation of indole formation during the oolong tea manufacturing process. This is the first report on the involvement of DNA methylation in the regulation of aroma compound formation in tea leaves exposed to postharvest stresses.
Keywords: CAMELLIA SINENSIS; DNA METHYLATION; EPIGENETIC REGULATION; STRESS; POSTHARVEST PROCESSING; TEA AROMA; VOLATILE